Exploring the Dynamic Interplay Between Foreign Language Enjoyment and Learner Engagement With Regard to EFL Achievement and Absenteeism: A Sequential Mixed Methods Study - Guo, Yunxian (Frontiers in Psychology, 2021)
Scholarly attention to the feeling of enjoyment experienced in second language acquisition (SLA) has sharply increased in the past five years owing to its positive effect on facilitating academic outcomes as well as promoting language learners’ well-being. This sequential mixed methods study aims to examine the interplay between Foreign Language Enjoyment (FLE) and Learner Engagement (LE) as well as their combined effects on participants’ EFL achievement and absenteeism. To this end, we administrated a questionnaire containing the adapted FLE Scale and the four-aspect engagement inventory among 707 Chinese university students and a semi-structured interview among 28 of them. Statistical analysis revealed that FLE was highly and positively correlated with LE, and the causal relationship between the two constructs was reciprocal. Furthermore, both FLE and LE had low correlations with participants’ academic achievements, but no significant correlation was found between FLE or LE and absenteeism. However, a higher level of FLE-social was associated with a lower level of absenteeism. Finally, no gender differences were found either in the level FLE or in that of LE. The thematic analysis indicated that FLE was subject substantially to teacher-related variables and the second most significant attractor of FLE was FLE-self. Analysis of the trends of LE indicated that Chinese EFL learners preferred to engage themselves in their English study more emotionally, behaviorally, and cognitively than agentically. Pedagogical implications of the findings for EFL practitioners are also discussed, and suggestions for future research are offered.